2008
DOI: 10.1111/j.1523-1739.2008.01044.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Extinction Risk: IUCN's System for Classifying Threatened Species

Abstract: The International Union for Conservation of Nature (IUCN) Red List of Threatened Species was increasingly used during the 1980s to assess the conservation status of species for policy and planning purposes. This use stimulated the development of a new set of quantitative criteria for listing species in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
999
4
32

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 1,132 publications
(1,047 citation statements)
references
References 112 publications
(129 reference statements)
12
999
4
32
Order By: Relevance
“…The N e is often an important parameter for endangered species management and policy [28]. The utility of our N e estimates for evaluating the short-term genetic status of the Kirtland’s warblers depends on the accuracy and precision of our contemporary N e estimates Simulations suggest that it is difficult to obtain a precise estimate of N e when the true N e is >400 because at those sizes of N e , sampling error is large compared to the strength of the drift induced shifts in heterozygosity and linkage disequilibrium [21,29].…”
Section: Resultsmentioning
confidence: 99%
“…The N e is often an important parameter for endangered species management and policy [28]. The utility of our N e estimates for evaluating the short-term genetic status of the Kirtland’s warblers depends on the accuracy and precision of our contemporary N e estimates Simulations suggest that it is difficult to obtain a precise estimate of N e when the true N e is >400 because at those sizes of N e , sampling error is large compared to the strength of the drift induced shifts in heterozygosity and linkage disequilibrium [21,29].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that migrants have more specialized diets than nonmigrants (e.g., diet specialization hypothesis; Boyle, Conway, & Bronstein, 2011). We expect migrants to have narrower diet breadth than nonmigrants, especially for tracking migrants, which follow specific resources rather than using alternative ones in a single place.Red List—Threat assessment categorization according to the IUCN Red List (Mace et al., 2008). We ran our analyses with the Red List category coded in two ways.…”
Section: Methodsmentioning
confidence: 99%
“…Some taxa, such as non-vascular plants and most invertebrates, were underrepresented in N RLTSs and SRLTSs (Köppel et al 2003, Zamin et al 2010), leading to a corresponding bias in conservation policies (Mace et al 2008, Martín-López et al 2011. While the focus is on species for which data is available, the lack of currently available data may conceal greater threats to other species (McKinney 1999).…”
Section: Nrlts and Srlts Coveragementioning
confidence: 99%
“…National and subnational actors mainly use RLTSs for prioritizing species for protection. Nevertheless, a confusion persists between risk of extinction and conservation priorities or rarity (Miller et al 2007, Fitzpatrick et al 2007, Mace et al 2008) that can affect RLTS efficiency and constrain support from policymakers (Possingham et al 2002, Lamoreux et al 2003. As a prioritization tool, RLTSs must be associated with other factors such as national responsibility and opportunities for action (Keller & Bollmann 2004, Rodríguez et al 2004, Schatz et al 2014, Schmeller et al 2014.…”
Section: Role Of Rltss In Biodiversity Conservation Programs and Polimentioning
confidence: 99%
See 1 more Smart Citation